Critical Care Nutrition from a Metabolic Point of View: A Narrative Review - Oami, Takehiko; Yamamoto, Akiyuki; Ishida, Shigenobu; Kondo, Kengo; Hata, Nanami; Oshima, Taku (Nutrients, 2025)
Background: Critical illness induces profound metabolic alterations, characterized by a hypermetabolic state, insulin resistance, protein catabolism, and gut barrier dysfunction, which contribute to increased morbidity and mortality. Emerging evidence highlights the role of the gut microbiome and its metabolites in modulating systemic inflammation and immune responses during critical illness. This narrative review explores the metabolic evolution of critically ill patients, the impact of gut dysbiosis on disease progression, and the potential role of nutrition in modulating metabolism and improving patient outcomes. Methods: A comprehensive literature search was conducted across PubMed and Google Scholar for articles published up to February 2025. Search terms included “critical illness”, “metabolism”, “gut microbiota”, “nutrition”, and related keywords. Articles published in English addressing metabolic alterations, microbiome changes, and nutritional strategies in critically ill patients were included. After screening for eligibility, relevant articles were synthesized to outline current knowledge and identify gaps. Results: Metabolic changes in critical illness progress through distinct phases, from catabolism-driven hypermetabolism to gradual recovery. Gut dysbiosis, characterized by a loss of microbial diversity and increased gut permeability, contributes to systemic inflammation and organ dysfunction. Nutritional strategies, including enteral nutrition, probiotics, prebiotics, and metabolomics-driven interventions, may help restore microbial balance, preserve gut barrier integrity, and modulate immune and metabolic responses. Future nutrition therapy should focus on metabolic modulation rather than solely addressing nutrient deficits. Conclusions: Advances in gut microbiome research and metabolomics offer new avenues for personalized nutrition strategies tailored to the metabolic demands of critically ill patients. Integrating these approaches may improve clinical and functional recovery while mitigating the long-term consequences of critical illness.